Researches on Ecological Solidification and Melioration Effects of Plants on Silty Soft Soil. Issue 1 (1st April 2022) - Wang, Tao; Zhu, Qi; Bi, Shiming; Wang, Jing; Fu, Pin
Abstract: Dredged soil from river and lake is a typical silty soft soil, which has a high potential for farmland utilization. However, the newly dredged soil generally has high water content and poor engineering properties, therefore, it must be dehydrated and solidified before utilization. The traditional dehydration and solidification methods have disadvantages such as high energy consumption and secondary pollution risk. A method of soil solidification and amelioration by using plants is explored in this research. Four species of Pennisetum hydridum, Sorghum bicolor × Sorghum sudanense, Typha angustifolia, and Zea mays, were used as the research objects, planted in silty soft soil. The solidification and amelioration effects of different plants were studied by observing the changes in soil mechanics and physicochemical properties before and after the experiment. The results showed that: all the four tested species showed soil solidification effects in different degrees, the Pennisetum hydridum with 0.5m planting distance showed the best effect. The four tested species increased the soil organic matter content in varying degrees, among which the mix-planting of Pennisetum hydridum and Typha angustifolia showed the best effect. Pennisetum hydridum can increase the soil alkaline hydrolyzable nitrogen(AH-N) content, Typha angustifolia can simultaneously increase the soil available phosphorus and available potassium content. In addition, the four tested species showed varying degrees of amelioration effects on physical properties. The Pennisetum hydridum shows the best amelioration effect, followed by Sorghum bicolor × Sorghum sudanense. In summary, it is feasible to use plants to solidify and ameliorate silt soft soil, which is beneficial to realize the resource utilization of dredged soil, especially suitable for agricultural land use.